Institutional framework of youth organization in local self-government units in the Republic of Serbia: Problems and potential solutions - Milenković Dejan; Petrović Agatina (Srpska Politička Misao)
The paper analyzes the institutional mechanisms of youth participation in the creation and implementation of public policies, with a focus on the local level. The paper highlights the importance of young people's social capital for the development of a healthy and sustainable community. Through active participation, formal and informal association, and continuous communication with local institutions, young people develop opportunities to express and fulfill their rights and needs, while contributing to the overall development of the local community. The Law on Youth, which was adopted in the Republic of Serbia over 10 years ago, determines the ways of organizing youth, but there have been numerous problems in its implementation. Using the metod of content analysis of legal norms, primarily the Law on Youth and National Youth Strategies, institutional problems of youth organization are presented, and specific normative solutions that could become part of a new youth law are proposed. Special emphasis is placed on the institutional framework of youth organization at the local level, where youth offices, youth spaces and youth work are analyzed. The results of the analysis have shown numerous problems resulting from unclear and insufficiently developed provisions of the law on these issues. Additionally, the paper presents comparative solutions for the same issues in certain European Union member states and Western Balkans countries.